Penerapan Model Discovery Learning Terhadap Pembentukan Karakter Siswa yang Berorientasi Higher Order Thinking (Hots) di Sekolah Dasar - Putu Ida Arsani Dewi (STAHN Mpu Kuturan Singaraja, 2020)
The formation of character education-oriented HOTS in elementary school is a new breakthrough in developing the character of students. The purpose of this study is to form the character of students and shaping the students ' high level thinking. This research is a descriptive research using a qualitative approach. The results showed that the formation of character education student-oriented HOTS can be implemented in accordance with the target learning outcomes. The value of the characters that formed the values of discipline, religious, responsible, and honest. Integration in the classroom by integrating the education oriented HOTS in LESSON plans and implemented during the learning while the intergasi outside the classroom, i.e. with a refraction value of a religious character, habituation character value of discipline come to school on time, planting the character value of responsibility in the management of the class, and the value of honest character by writing daily activities of the students. Keywords: Character, HOTS, Elementary School